Answer:
y intercept = -2
x intercepts = -2,-1,1
Explanation:
f(x) = x^3 + 2x^2 -x-2
Set this equation equal to zero to find the x intercepts.
Factoring by grouping
0 =x^3 -x +2x^2 -2
= x( x^2-1) +2(x^2-1)
Factoring out the (x^2-1)
0= (x^2-1) (x+2)
Factoring the first term using the difference of squares (a^2-b^2) = (a-b)(a+b)
0 = (x-1) (x+1) (x+2)
Using the zero product property
x-1 = 0 x+1 = 0 x+2 =0
x=1, x=-1 x=-2
The x intercepts are -2, -1, 1
To find the y intercepts, set x=0
y = x^3 + 2x^2 -x-2
y = 0 -2
y = -2